PERANCANGAN SISTEM INFORMASI AKUNTANSI BERBASIS WEB PADA DESA MULYAHARJA - Ramadhanti, Resti Jayeng; Rosyanti, Novi; Ginoga, Lesia Fatma; Syahwani, Asty Khairi Inayah (Ekonomi & Bisnis, 2025)
This study addresses the issues of manual financial management in Desa Wisata Mulyaharja, which is often ineffective, leading to recording errors and difficulties in financial monitoring. This research aims to design a web-based accounting information system to improve the efficiency and effectiveness of the village’s economic management. The method used is the Waterfall model, which includes the stages of planning, analysis, design, implementation, and testing. The study results indicate that this web-based system can automate the processes of financial recording and reporting, reduce the risk of manual errors, expedite decision-making, and enhance the accuracy and transparency of accounting data